Teachers’ implicit beliefs and LGBTQIA+ students’ school dropout: a Queer Media Education approach - Messina, Salvatore; Mascitti, Marika (Form@re - Open Journal per la formazione in rete, 2025)
This article examines the influence of teachers’ implicit beliefs on early school leaving among LGBTQIA+ students, highlighting the role of heteronormative norms and unconscious biases in shaping the school climate and students’ sense of belonging. Adopting the Queer Critical Media Literacies framework (van Leent & Mills, 2017), queerness is understood as a critical lens capable of deconstructing normative categories and institutional power structures. Within this perspective, schools are reimagined as spaces of cultural renegotiation, where inclusive educational practices – such as media education and game-based learning – contribute to the dismantling of dominant narratives. Queer education, conceived as a process of critical resignification, fosters new forms of recognition and educational relationships grounded in equity, inclusion, and social justice. Convinzioni implicite dei docenti e abbandono scolastico di studentə LGBTQIA+: un approccio di Queer Media Education. L’articolo esamina l’influenza delle credenze implicite dellə docenti sull’abbandono scolastico precoce di studentə LGBTQIA+, sottolineando il ruolo delle norme eteronormative e dei bias inconsci nel modellare il clima scolastico e il senso di appartenenza. Adottando il framework delle Queer Critical Media Literacies (van Leent & Mills, 2017) la queerness è intesa come lente critica capace di decostruire categorie normative e assetti di potere istituzionali. In questo orizzonte, la scuola viene riconfigurata come spazio di rinegoziazione culturale, in cui pratiche educative inclusive – come l’educazione nei/ai media e il game-based learning – contribuiscono alla decostruzione delle narrazioni dominanti. L’educazione queer, intesa come processo di risignificazione critica, promuove nuove forme di riconoscimento e relazioni educative orientate all’equità, all’inclusione e alla giustizia sociale.